1. The problem statement, all variables and given/known data I need to show that the lim n->inf ( [(1/n) * sum from k=1 to n of ln(k) ] - ln(n) ) is equal to the lim n->inf ( (1/n) sum from k=1 to n of ln(k/n) ) 3. The attempt at a solution I showed that the sum of ln(n) from k=1 to n is ln(n!) using ln(a) + ln(b) = ln(a+b). I am not sure how to get from (1/n)ln(n!) - ln(n) to (1/n)sum-ln(k/n). I apologize for the non-tex stuff.... but I am not sure how to do some of the symbols for this in tex yet. Thank you for your help.